Povos in/visíveis: imagens dos povos no cinema brasileiro contemporâneo - Luz, Júlio César Alves da (2018)
This study has as purpose the investigation of the conditions of visibility of people regarding the images of contemporary cinematographic production in Brazil. Getting back to the point that bursts with the critical realism in the context of the emergence of the modern cinema in the country and it is lifted to the central interest in the aesthetic ideological project of a generation deeply involved in the conflicts of the political sphere, this project relocates it in the present in order to rethink the forms of visibility of people in recent Brazilian films. We problematize the common images that, by designating them, actually make people invisible, in order to find the images of the common in which they effectively appear with their differences and under real visibility conditions. Starting from the critics on the way of a visibility that reduces them to invisibility, what we propose on this theses, when examining the images of people in the films that compose the analytical corpus of the research, is that we see people feature in a dialectic between the visible and invisible, stressed between what they show and what they elide, between the senses of what is included and what is excluded. For this purpose, we examine the images in their compositional aspects, especially the frame and the mise-en-scène, identified as the aesthetic-political operations that define the ways in which people are shown in the film images.